Electrochemical Abatement of Analgesic Antipyretic 4‐Aminophenazone using Conductive Boron‐Doped Diamond and Sub‐Stoichiometric Titanium Oxide Anodes: Kinetics, Mineralization and Toxicity Assessment. Issue 6 (14th January 2019) - Ganiyu, Soliu O.; Oturan, Nihal; Trellu, Clément; Raffy, Stéphane; Cretin, Marc; Causserand, Christel; Oturan, Mehmet A.
Abstract: The oxidation ability of two prominent eco‐friendly electrochemical advanced oxidation processes (EAOPs), namely anodic oxidation with H2 O2 generation (AO‐H2 O2 ) and electro‐Fenton (EF) for complete abatement of acidic solution of 4‐aminophenazone (4‐APZ) has been investigated using conductive boron‐doped diamond (BDD) and sub‐stoichiometric titanium oxide (Ti4 O7 ) anodes and carbon‐felt cathode. The higher performance of EF compared to AO‐H2 O2 with either anode was demonstrated. In all trials, 4‐APZ was completely destroyed, following pseudo first‐order kinetics with the rate constant values increasing with applied current and higher values attained with BDD compared to Ti4 O7 anode at similar conditions. The absolute rate constant for the reaction between 4‐APZ and hydroxyl radicals was found to be 3.9±0.2×10 9  L mol −1  s −1 . Complete mineralization could be attained with BDD anode, whereas Ti4 O7 anode only showed excellent mineralization up to 94 % TOC removal. Therefore, Ti4 O7 anode can constitutes a promising anode material thanks to its lower manufacturing cost. Inorganic ions like NO3 − and HCO3 − at concentration up to 25 mM has no effect on mineralization efficiency during AO‐H2 O2, but the presence of Cl − even at lower concentration of 10 mM significantly reduced the TOC removal efficiency. The toxicity of the solution sharply increased at initial stage of treatment, corresponding to the formation of cyclic by‐products but their conversion to carboxylic acids due to longer treatment time involved a sharp toxicity decrease, thus ensuring overall detoxification. Abstract : Abatement of 4‐aminophenazone: complete degradation and excellent to total abatement of 4‐APZ is achieved by electrochemical treatment with higher efficiency obtained using boron doped diamond compared to Ti4 O7 as anode and electro‐Fenton process compared to anodic oxidation at similar experimental conditions.